Cusp overlap technique for self‐expanding valves: Refining technique defining outcomes. Issue 5 (9th March 2023) - Seth, Ashok; Chopra, Manik
Key Points: Cusp overlap (COV) technique for Transcatheter Aortic Valve Implantation (TAVI) with self‐expanding valves (SEV) has been proposed to enable accurate and high placement of valves to decrease permanent pacemaker implantation (PPI). Metanalysis of published experience with COV technique confirms decrease in PPI rates without compromising on safety. COV technique could be considered the technique of choice for implantation of SEV.